A blind demodulation algorithm of random codes on carrier under low signal noise ratio by Morlet wavelet. (6th March 2020) - Huang, Wei; Zhao, Xiangmo; Wang, Chao
This paper proposes a novel blind demodulation algorithm of random codes on carrier under low signal noise ratio (SNR) by using continuous wavelet transform. We chose Morlet wavelet with similarity and symmetry. The proposed algorithm can demodulate random codes on carrier under low SNR without any prior knowledge. Simulation results show that the bit error rate (BER) curve of the existing blind demodulation algorithms of direct sequence spread spectrum is above the theoretical BER curve of the coherent demodulation. Simulation result of new algorithm shows that BER curve of the blind demodulation of the wavelet transform is below the theoretical BER curve of coherent demodulation. The novel blind demodulation algorithm allows to obtain an 8 dB gain in SNR terms compared with that obtained by the theoretical coherent modulation when SNR is 10 –4 .